Mechanical Surface Area of Prosthetic Heart Valve: Adverse Clinical Impact of Large Mechanical Valve in Mitral Position. Issue 6 (November 2018) - Cho, Yang Hyun; Sung, Kiick; Kim, Wook Sung; Kim, Jae-Hun; Kim, Sung Mok; Park, Pyo Won
Abstract : Although thromboembolic accidents are serious adverse events associated with mechanical mitral valves, there have been no studies on the clinical impact of the large mechanical surface areas (MSAs) of mechanical mitral prostheses. Between 1995 and 2010, 488 consecutive adult patients underwent isolated mechanical mitral valve replacement. We measured the MSA via three-dimensional computed tomography for each prosthesis. Mean patient age was 50.6 ± 11.1 years. The mean body surface area (BSA) and MSA index (MSAI, MSA/BSA) were 1.6 ± 0.17 m 2 and 12.9 ± 1.7 cm 2 /m 2, respectively. The patients were divided into two groups according to the median MSAI. Patients in the high MSAI group had higher indexed left ventricular end-diastolic dimensions and smaller BSAs. The multivariate analysis demonstrated that old age, New York Heart Association class III or IV, and high MSAI were independent predictors of death. With respect to thromboembolic complications, New York Heart Association class III or IV and high MSAI were identified as independent risk factors. There were 11 patients (3%) with mean pressure gradients across the mitral valve greater than 6 mm Hg 1 year after operation. A large MSA relative to patient size was identified as a predictor of poor clinical outcome after mechanical mitral valve replacement.